Shallow-water anomuran and brachyuran crabs (Crustacea: Decapoda) from southern Bahia, Brazil - Alemida, Alexandre Oliveira de (2010)
The objective of this study was to determine the taxonomic composition and ecological aspects of decapod crustacean species belonging to the infraorders Anomura and Brachyura in shallow marine and estuarine waters from southern Bahia, a coastline about 640 km in extent, corresponding to approximately 7% of the Brazilian coast. Sixteen species of the infraorder Anomura and 68 of the infraorder Brachyura are reported for the study area. The most important families in terms of number of species were the Panopeidae with 11 species, and the Ocypodidae and Portunidae with 9. Among the Brachyura, the southern distribution of the species Austinixa leptodactyla Coelho, 1997 (Pinnotheridae), endemic to Brazil, is extended from the coast of Sergipe to Bahia (Prado, Cumuruxatiba Beach, 17°06'18.6"S, 39°10'50.4"W). The ocypodid Uca (Leptuca) cumulanta Crane, 1943 and also the pinnotherids Austinixa aidae (Righi, 1967) and Fabia byssomiae (Say, 1818) are reported for the first time from the Bahia coast. The specimen of F. byssomiae examined was collected in the mantle cavity of the clam Macoma constricta (Bruchière, 1792) (Bivalvia: Tellinidae), a new host record for the species.